O povijesno-književnim (re)konstrukcijama Matoša - Škvorc, Boris (Wydawnictwo Nauka i Innowacje, 2014)
This article deals with the constructions of „Matoš” in Croatian histories of literature. Central for the study is Alum Munslow’s thesis that history cannot be „non-narrative”. In that respect the relationship between hi/story and narrative genre is studied on examples of how the „character” of Antun Gustav Matoš, one of the most famous Croatian writers from the beginning of twentieth century, is both perceived and constructed in historical narrative and in philological context that is discursively circled by the narrative.
About the [Re]Constructions of Matoš in Histories of Literature
Keywords: Antun Gustav Matoš; narration; history and story; nation; ideologemes and mythologemes; philological level of analytical process; reconstruction and deconstruction in reading literary history